NMR assignment of intrinsically disordered self-processing module of the FrpC protein of Neisseria meningitidis - Kubáň, Vojtěch; Nováček, Jiří; Bumba, Ladislav; Žídek, Lukáš (Biomolecular NMR assignments, 2015)
The self-processing module (SPM) is an internal segment of the FrpC protein (P415-F591) secreted by the pathogenic Gram-negative bacterium Neisseria meningitidis during meningococcal infection of human upper respiratory tract. SPM mediates 'protein trans-splicing', a unique natural mechanism for editing of proteins, which involves a calcium-dependent autocatalytic cleavage of the peptide bond between D414 and P415 and covalent linkage of the cleaved fragment through its carboxy-terminal group of D414 to [Formula: see text]-amino group of lysine residue within a neighboring polypeptide chain. We present an NMR resonance assignment of the calcium-free SPM, which displays characteristic features of intrinsically disordered proteins. Non-uniformly sampled 5D HN(CA)CONH, 4D HCBCACON, and HCBCANCO spectra were recorded to resolve poorly dispersed resonance frequencies of the disordered protein and 91 % of SPM residues were unambiguously assigned. Analysis of the chemical shifts revealed that two regions of the intrinsically disordered SPM (A95-S101 and R120-I127) have a tendency to form a helical structure, whereas the residues P1-D7 and G36-A40 have the propensity to adopt a [Formula: see text]-structure.
Keywords: nukleární magnetická rezonance biomolekulární; Protein Structure, Secondary; Membrane Proteins; Bacterial Proteins; Nuclear Magnetic Resonance, Biomolecular; Intrinsically Disordered Proteins; Neisseria meningitidis; vnitřně neuspořádané proteiny; membránové proteiny; sekundární struktura proteinů; bakteriální proteiny